Determinants of Employee Performance at Public Health Centers - Sefnedi; Reni Yuliviona; Miza Sulasmi (International Journal of Engineering and Management Research, 2023)
Employee performance has become the center of attention for academics and practitioners. However, until now, the determinants of employee performance are still being debated. This study investigates the determinants of employee performance at public health center. The population of this study was all employees at the health center in the Kuranji sub-district, Padang, West Sumatra, totaling 118 employees. In data analysis, this research uses SEM-PLS software. This study found that organizational culture had a positive and significant effect on work motivation and organizational commitment but had no effect on employee performance. Work motivation has a positive and significant effect on organizational commitment and employee performance. Furthermore, organizational commitment also positively and significantly influences employee performance.